2013
DOI: 10.1002/jqs.2667
|View full text |Cite
|
Sign up to set email alerts
|

Deeply rooted glaciotectonism in western Denmark: geological composition, structural characteristics and the origin of Varde hill‐island

Abstract: We investigate a hill-island in western Denmark, a major cupola-hill-type thrust complex generated by ice-marginal glaciotectonism. The study uses a unique dataset of densely spaced airborne electromagnetic data, high-resolution seismic data and borehole information to document the complexity of deeply rooted thrust sheets comprising Miocene to middle Pleistocene deposits. The deformation spans at least 150 m of sediment thickness, placing this complex among the largest glaciotectonic features on record. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…We found that the RF residuals exhibit a spatial correlation explicitly in the hill island landscape in western Denmark, indicating that one or more essential covariates may be missing in the current model setup. As outlined by Høyer et al (), the geomorphological setting of the hill islands in western Denmark is very complex due to several sequences of glaciotectonic deformation and erosion. A high‐resolution groundwater model or a detailed geomorphological map may resolve some of these issues, but further investigations are needed to identify the crucial covariates needed to improve the RF in the hill island landscape.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the RF residuals exhibit a spatial correlation explicitly in the hill island landscape in western Denmark, indicating that one or more essential covariates may be missing in the current model setup. As outlined by Høyer et al (), the geomorphological setting of the hill islands in western Denmark is very complex due to several sequences of glaciotectonic deformation and erosion. A high‐resolution groundwater model or a detailed geomorphological map may resolve some of these issues, but further investigations are needed to identify the crucial covariates needed to improve the RF in the hill island landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Høyer et al . () have noted evidence of deep‐seated glaciotectonism in Denmark, indicative of loading by thick ice, and thus inferred that past ice margins were steep, the ice exceeding 1000 m thickness within 6 km of its margin. It is thus plausible that this region was covered on at least one occasion by thick enough ice to replicate ∼1000 m of sediment loading, thus explaining Japsen's (1998) results.…”
Section: Discussionmentioning
confidence: 99%
“…Although Denmark was only partly ice-covered during MIS 6 and MIS 2, the ice was more extensive during the Elster glaciation (MIS 12) and apparently again in MIS 8, the Treldenaes Glaciation (Houmark-Nielsen, 2011). Høyer et al (2013) have noted evidence of deepseated glaciotectonism in Denmark, indicative of loading by thick ice, and thus inferred that past ice margins were steep, the ice exceeding 1000 m thickness within 6 km of its margin. It is thus plausible that this region was covered on at least one occasion by thick enough ice to replicate $1000 m of sediment loading, thus explaining Japsen's (1998) results.…”
Section: Discussionmentioning
confidence: 99%
“…We present a field case from the area of Ølgod, Denmark, which has been the object of dense geophysical mapping with electrical, electromagnetic and seismic methods in connection with the KOMPLEKS project 2008–2012 aimed at mapping large‐scale geological structures to improve hydraulic modelling (Høyer et al ., 2011, 2013a, 2013b, 2014; He et al ., 2013). In this paper, we focus on the airborne transient electromagnetic survey carried out with the SkyTEM system in 2006 and 2009 (Sørensen and Auken, 2004; Auken et al ., 2006, 2009, 2017) and inverted with the WorkBench program (Auken et al ., 2014).…”
Section: Field Example: Using Airborne Em Data To Estimate Clay Thicknessmentioning
confidence: 99%